Implementation of Screen Archery Studio for Realistic Screen Sports Experiences - Bang, Green; Kil, Youngik; Lee, Sangwon; Ko, Ilju (International Journal of Engineering and Technology, 2018)
Background/Objectives: The need for realistic indoor screen sports has increased due to environmental and social factors. This paper aims to develop a screen archery studio where the general public may enjoy archery, an elite sport.Methods/Statistical analysis: A studio for screen archery consists of a video output component, including a projector and screen, and a system recognition component, comprised of a VR archery shooter, IR camera, and NFC reader device. The VR archery shooter is a device that implements virtual reality in places where real arrows may not be used for safety reasons. The realistic studio for screen archery has an advantage in that it can provide dynamic game contents in a narrow space. The provided content has two modes: Olympic game mode and hunting mode.Findings: The studio in the proposed system provides elements that immerse players in the game as well as the experience of sports events that are not easily experienced in daily living. In particular, the recurve bow used in the VR archery shooter is the same equipment as is used in actual indoor archery fields or games to increase the feeling of realism.Improvements/Applications: Although the provided content is currently limited to Olympic and hunting modes only, more active screen archery content is in development, including moving archery targets, which are the goal of a future study.Â Â Â